Pengaruh Model Pembelajaran Ekspositori Berbantuan Advance Organizer Terhadap Hasil Belajar Siswa Kelas V Mata Pelajaran IPA Macam-Macam Sumber Energi Di SD Islam Nurus Syamsi - Adelia Anggraini Lestari (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This study aims to investigate the effect of the Advance Organizer Assisted Expository Learning Model on the learning outcomes of fifth grade students in science subjects with a focus on various energy sources at SDI NURU SYAMSI. The research method used was the One Group Pretest-Posttest Design. The participants in this study were 25 fifth grade students at SDI NURUS SYAMSI. The study was conducted in one group with a pretest-posttest design, in which students were measured for their initial ability (pretest) before being given treatment, namely the Advance Organizer Assisted Expository Learning Model. After the treatment, students were then measured again (posttest) to see an increase in learning outcomes after applying the method. The results showed that there was a significant increase in learning outcomes in science subjects about various energy sources after the application of the Advance Organizer Assisted Expository Learning Model. The Expository Learning Model Assisted by Advance Organizer as an alternative learning method is expected to help improve student learning outcomes in science subjects about various energy sources. Although this study found positive results, the authors are aware that there are some limitations in this study, such as the limited number of samples. Therefore, the authors recommend further research to strengthen and generalize the findings obtained.